Analysis of Factors Affecting the Quality of Local Government Financial Statements - Widaryani, Heylmi Umi; -, Kiswanto (Accounting Analysis Journal, 2020)
Testing the determinants or factors that influence the quality of LKPD is the aim of this study. All State Civil Servants (ASN) working in 51 Regional Organization (OPD) of Klaten Regency were made as research populations. The entire population was only 83 respondents who were selected as samples with purposive sampling technique in their selection. Structural Equation Model (SEM) smartPLS is a analysis tool of research data. The results showed that the effectiveness Regional Financial Accounting System (SAKD), and the effectiveness Internal Control System (SPI) had a positive and significant effect while organizational commitment did not have a positive and significant effect on quality of local government financial reports. The effectiveness of SAKD has a positive and significant effect on the effectiveness of SPI. The effectiveness SAKD, and the effectiveness SPI have a positive and significant effect on organizational commitment. The results of the study also prove that the effectiveness SPI can mediate but organizational commitment cannot mediate the relationship of regional financial accounting system to the quality of LKPD. The effectiveness SAKD and the effectiveness SPI play an important role in the quality of LKPD is the conclusion of this study.